Propafenone in restoring sinus rhythm among patients with persistent atrial fibrillation. PROMETEY – an open, multicenter, pilot study performed in the Russian Federation (part II) - I. G. Fomina; A. I. Tarzimanova; A. V. Vetluzhsky; A. A. Abramova (Кардиоваскулярная терапия и профилактика)
Aim. To study efficacy and safety of propafenone (450 mg/d per os) in maintaining sinus rhythm among patients with persistent atrial fibrillation (AF). Material and methods. The study included 200 patients with persistent AF, aged 39-68 (mean age 56.4±4.2 years), from 10 Russian regions. For AF paroxysm prevention, all patients received propafenone (Propanorm, 450 mg per os, 3 times per day) for 9 months. Results. Propafenone (450 mg/d) restored sinus rhythm in 148 patients (74%) after one month of treatment, in 122 (61%) after 3 months, and in 90 (45%) after 9 months. Propafenone was effective and well tolerated: during 9-month therapy, only 8 patients (4%) complained of dyspepsia, which regressed without additional therapy or treatment discontinuation. Arrhythmogenic effects of propafenone were not registered. In 7 patients (3.5%), PQ interval increased significantly, by 18% comparing to baseline, but the parameter stayed in the normal range. Moderate increase of QT interval (+28%), without being over 460 ms, was observed in 8 patients (4%), and did not require therapy discontinuation. Conclusion. According to the results of open, multi-center study “PROMETEY”, propafenone (450 mg/d per os) was effective and safe for maintaining sinus rhythm in patients with persistent AF. In patients with normal left ventricular ejection fraction, propafenone did not affect inotropic myocardial function.